Premature coronary artery disease and severe hypertriglyceridemia in a patient with monogenic diabetes: a case report - V. I. Mikhailina; A. N. Meshkov; A. V. Kiseleva; A. I. Ershova; M. Zaichenoka; E. S. Luboyatnikova; M. S. Pokrovskaya; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2023)
Aim. Maturity- onset diabetes of the young (MODY) is a group of monogenic diseases with an autosomal dominant inheritance. This is a rarely diagnosed disease, occurring in 1 of 10 thousand adults and in 1 of 23 thousand children. Brief description. We present a case report of a patient with a monogenic diabetes HNF4A-MODY, severe hypertriglyceridemia, progressive premature coronary artery disease and a HNF4A gene pathogenic variant (ENST00000316099.8:c.1145dup).Discussion. This case demonstrates the effectiveness of triple hypoglycemic therapy, including empagliflozin for the treatment of monogenic diabetes. Despite the fact that the patient with diabetes reached the target glycated hemoglobin level, the combination of the disease with other cardiovascular risk factors (hypertension, hypertriglyceridemia, obesity, smoking, male sex) led to the progression of coronary and peripheral atherosclerosis. Considering the data of genetic testing, returning to sulfonylurea therapy should be considered. It is important for patient to follow a strict lipid-lowering diet and taking combination lipid-lowering therapy (rosuvastatin, fenofibrate and omega-3 polyunsaturated fatty acids) in order to achieve the target level of low-density lipoprotein cholesterol <1,4 mmol/l and triglycerides <1,7 mmol/l.